Theoretical and experimental study of methane partial oxidation tosyngas in catalytic membrane reactor with asymmetricoxygen-permeable membrane - Shelepova E. V.; Vedyagin A. A. Aleksey Anatolievich; Sadykov V. A.; Mezentseva N. V.; Fyodorova Yu. K.; Smorygo O. L.; Klyonov O. P. Oleg Pavlovich; Mishakov I. V. Iljya Vladimirovich (2016, 2016)
Title screen